Preparation method of mother-child type urine storage bag
By using polylactic acid and polyhydroxy fatty acid ester substrates, combined with the esterification reaction of chitosan and polyurethane, and the polytetrafluoroethylene coating, the problem of precipitating toxic functional groups in the urine storage bag in the urine environment is solved, and the Higher wear resistance, antibacteriality and patient comfort.
Patent Information
- Application Number
- CN202411585653.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-08
- Publication Date
- 2025-02-07
- Estimated Expiration
- 2044-11-08
AI Technical Summary
Existing urine storage bags are prone to precipitation of toxic or pathogenic functional groups in the dissolved environment of urine, resulting in urinary tract infection or immune lesions in the patient.
Polylactic acid and polyhydroxy fatty acid esters are used as substrates, and the polymer produced by the esterification reaction is carried out by adding chitosan, antioxidants, calcium carbonate micropowder and polyurethane to enhance structural stability and antibacterial properties, and coated on the surface. Coated with polytetrafluoroethylene coating to improve hydrophobicity and corrosion resistance.
It improves the wear resistance, corrosion resistance and antibacterial properties of the urine storage bag, reduces the long-term contact between urine and urine storage bag, reduces the risk of infection and inflammation, and improves the comfort of the patient.
Smart Images

Figure SMS_1 
Figure SMS_2 
Figure SMS_3
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of urine storage bags, and in particular to a method for preparing a mother-and-child type urine storage bag. Background Art
[0002] Urine storage bag (also called urine collection bag or urine collection bag) is a medical device used to collect and store urine, which is widely used in clinical medicine, nursing and patients' daily life. Its main purpose is to provide convenient and hygienic urine collection solutions for patients with indwelling catheters, postoperative patients and other people who cannot urinate normally.
[0003] The normal pH value of human urine ranges from about 4.5 to 8.0, which is in the range of strong acidity to weak alkalinity. The pH value range of urine of some patients with urinary system or metabolic system diseases is wider. Existing urine storage bags are generally made of resin materials, and wear-resistant resin materials are prone to precipitate some toxic or pathogenic functional groups in the dissolution environment of urine. The functional group molecules diffuse upward along the catheter, which may cause biochemical stimulation to the mucous membranes in the patient's urethra, bladder, ureters and other urinary system mucosa, causing urinary system infection or immune lesions in patients.
[0004] Therefore, in order to solve the above problems, it is necessary to design a method for preparing a mother-child urine storage bag. Summary of the invention
[0005] The invention overcomes the shortcomings of the prior art and provides a method for preparing a mother-and-child type urine storage bag.
[0006] To achieve the above object, the technical solution adopted by the present invention is: a method for preparing a mother-child type urine storage bag, comprising the following steps:
[0007] Step S1, using 40-50 parts by weight of polylactic acid and 20-25 parts by weight of polyhydroxyalkanoate as a substrate, adding 3-5 parts by weight of chitosan, 0.1-0.5 parts of an antioxidant, and 1-2 parts of calcium carbonate powder for drying, and mixing them evenly after drying to obtain a mixed solid material, and sequentially adding a plasticizer, a solubilizer, and 3-7 parts by weight of polyurethane to the mixed solid material, and controlling the weight parts of the plasticizer and the solubilizer, and mixing them evenly to obtain a mixture;
[0008] Step S2, heating the mixture to a molten state, cooling it, and pelletizing it;
[0009] Step S3, pouring the pellets into an injection molding machine, controlling the injection molding temperature to a molten state, controlling the injection molding pressure, pressurizing the molten pellets, and then cooling to room temperature to obtain an opaque and flexible sub-bag product;
[0010] Step S4, washing and drying the opaque flexible sub-bag product, coating the surface with a polytetrafluoroethylene coating, and subjecting the sub-bag coated with the polytetrafluoroethylene coating to a heat-curing treatment;
[0011] Step S5, repeat the operations of step S1, step S2 and step S3 for preparing the material of the urine storage bag, and control the weight of the plasticizer, the weight of the solubilizer, the injection temperature and the injection pressure, perform pressure molding and then cool to room temperature to obtain a transparent and hard mother bag product.
[0012] In a preferred embodiment of the present invention, in step S1, the plasticizer is ethylene glycol dibenzoate, the antioxidant is butylated hydroxyanisole, and the solubilizer is polyethylene glycol.
[0013] In a preferred embodiment of the present invention, in step S1, the weight portion of the plasticizer is 7-9 parts, and the weight portion of the solubilizer is 2-4 parts.
[0014] In a preferred embodiment of the present invention, in step S1, the drying process is specifically drying at 75-80° C. for 3-4 hours.
[0015] In a preferred embodiment of the present invention, in step S3, the pellets are poured into an injection molding machine, heated to a molten state at an injection molding temperature between 150-160°C, the pressure is controlled at 80-100 MPa, and then cooled to room temperature of 25-28°C after pressure molding.
[0016] In a preferred embodiment of the present invention, in step S2, the mixture is fed into a twin-screw extruder for melt blending, the heating temperature is between 150-170° C., and the shear rate is controlled at 150-175 rpm.
[0017] In a preferred embodiment of the present invention, in step S4, the thermosetting treatment comprises: heating the sub-bag coated with the polytetrafluoroethylene coating at a temperature of 150-160° C. for 10-20 minutes.
[0018] In a preferred embodiment of the present invention, in step S5, the weight portion of the plasticizer is 4-6 parts, the weight portion of the solubilizer is 5-10 parts, the injection molding temperature is between 170-190° C., and the injection molding pressure is 100-120 MPa.
[0019] A mother-child urine storage bag, comprising: a child bag and a mother bag, and a one-way liquid valve connecting the child bag and the mother bag; the child bag and the mother bag are both made of the following raw materials in parts by weight: 40-50 parts of polylactic acid, 20-25 parts of polyhydroxyalkanoate, 3-5 parts of chitosan, 4-9 parts of ethylene glycol dibenzoate, 2-10 parts of polyethylene glycol, 0.1-0.5 parts of butylated hydroxyanisole, 1-2 parts of calcium carbonate micropowder, and 3-7 parts of polyurethane.
[0020] In a preferred embodiment of the present invention, the sub-bag and the mother bag are made of the following raw materials in parts by weight: 40 parts of polylactic acid, 20 parts of polyhydroxyalkanoate, 3 parts of chitosan, 4 parts of ethylene glycol dibenzoate, 2 parts of polyethylene glycol, 0.1 parts of butylated hydroxyanisole, 1 part of calcium carbonate powder, and 3 parts of polyurethane.
[0021] The present invention solves the defects existing in the background technology and has the following beneficial effects:
[0022] The present invention provides a method for preparing a mother-and-child urine storage bag, which uses polylactic acid and polyhydroxyalkanoate as substrates, and generates a polymer by adding polyurethane to react with the substrates to generate an esterification reaction, thereby enhancing the structural stability and compatibility of the urine storage bag, thereby improving the wear resistance and corrosion resistance of the urine storage bag. At the same time, the esterification reaction promotes the uniform dispersion of chitosan in the polymer matrix, reduces its agglomeration phenomenon, and enables the antibacterial activity of chitosan to effectively act on the surface, thereby improving the antibacterial performance.
[0023] The present invention enhances the mobility and fluidity of polyurethane and other polymer chains, and also enhances the reactivity of polyurethane by subjecting the sub-bags coated with polytetrafluoroethylene coatings to thermosetting treatment on the surfaces thereof, so that the polymer chains of polyurethane can be cross-linked to form a three-dimensional network structure, which can fill the microscopic defects and irregular shapes of the polytetrafluoroethylene coatings, thereby forming a dense bonding interface and enhancing the bonding force with the polytetrafluoroethylene coatings.
[0024] The present invention enhances structural stability and forms a denser structure through an esterification reaction between polyurethane and a substrate, effectively preventing water molecules from penetrating. The polytetrafluoroethylene coating is applied to change the chemical properties of the surface, thereby reducing the surface energy of the sub-bag, making it more difficult for water molecules to adhere to the surface, improving the hydrophobicity, and effectively preventing urine from adhering to the wall, allowing urine to flow more smoothly into the mother bag, while reducing the long-term contact between urine and the sub-bag, thereby reducing the risk of infection and inflammation. DETAILED DESCRIPTION
[0025] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0026] In the following description, many specific details are set forth to facilitate a full understanding of the present invention, but the present invention may also be implemented in other ways different from those described herein. Therefore, the protection scope of the present invention is not limited to the specific embodiments disclosed below.
[0027] A method for preparing a mother-and-child type urine storage bag comprises the following steps:
[0028] Step S1, using 40-50 parts by weight of polylactic acid and 20-25 parts by weight of polyhydroxyalkanoate as a substrate, adding 3-5 parts by weight of chitosan, 0.1-0.5 parts of an antioxidant, and 1-2 parts of calcium carbonate powder for drying, and mixing them evenly after drying to obtain a mixed solid material, and sequentially adding a plasticizer, a solubilizer, and 3-7 parts by weight of polyurethane to the mixed solid material, and controlling the weight parts of the plasticizer and the solubilizer, and mixing them evenly to obtain a mixture;
[0029] Step S2, heating the mixture to a molten state, cooling it, and pelletizing it;
[0030] Step S3, pouring the pellets into an injection molding machine, controlling the injection molding temperature to a molten state, controlling the injection molding pressure, pressurizing the molten pellets, and then cooling to room temperature to obtain a transparent and flexible sub-bag product;
[0031] Step S4, washing and drying the transparent and flexible sub-bag product, coating the surface with a polytetrafluoroethylene coating, and subjecting the sub-bag coated with the polytetrafluoroethylene coating to a heat-curing treatment;
[0032] Step S5, repeating the operations of step S1, step S2 and step S3 with the material for preparing the urine storage bag, and controlling the weight of the plasticizer, the weight of the solubilizer, the injection temperature and the injection pressure, performing pressure molding and then cooling to room temperature to obtain an opaque and hard mother bag product.
[0033] In the step S1, the plasticizer is ethylene glycol dibenzoate, the antioxidant is butylated hydroxyanisole, and the solubilizer is polyethylene glycol;
[0034] The weight parts of materials for preparing the urine storage bag are: 40-50 parts of polylactic acid, 20-25 parts of polyhydroxyalkanoate, 3-5 parts of chitosan, 1-2 parts of calcium carbonate powder, 4-9 parts of plasticizer, 2-10 parts of solubilizer, and 3-7 parts of polyurethane;
[0035] By using polylactic acid and polyhydroxyalkanoate as the substrate, the substrate is a bio-based polymer with excellent biocompatibility and biodegradability, and can be naturally degraded to reduce the environmental burden;
[0036] Chitosan is added in the preparation of urine storage bags. Chitosan has excellent antibacterial properties and interacts with bacterial cell membranes in the urine storage bags, thereby destroying the cell membranes and inhibiting bacterial growth, thereby improving the antibacterial properties of the urine storage bags.
[0037] The polyurethane is mixed with the substrate to undergo an esterification reaction to generate a polymer. The hydroxyl and isocyanate contained in the polyurethane form ester bonds and amino bonds in the reaction. During the reaction, the radical reacts with the hydroxyl and carboxyl functional groups in the substrate, and crosslinks with the functional groups of the polyurethane molecules, thereby forming a three-dimensional network structure. The radical and the crosslinking points of the functional groups connect different polymer chains through covalent bonds to form a three-dimensional crosslinked network structure, which not only enhances the mechanical strength of the material, but also improves its resistance to chemical corrosion.
[0038] In the esterification reaction, the hydroxyl groups in the polyurethane and the polymer can react with the carboxyl groups of chitosan to form ester bonds, which increases the chemical compatibility of chitosan with the matrix. The generated ester bonds enhance the interaction between chitosan and the polymer matrix, reduce the interfacial tension of chitosan in the matrix, and make it easier to disperse evenly in the polymer matrix. The esterification reaction can also promote the formation of a complex cross-linked network between chitosan and the polymer matrix, which not only provides a physical barrier, but also further prevents the aggregation of chitosan, so that a stable structure is formed between chitosan and the polymer, which contributes to the long-term release and persistence of the antibacterial components of chitosan.
[0039] By using calcium carbonate powder as a filler, the strength and hardness of the material can be improved; ethylene glycol dibenzoate as a plasticizer can improve the flexibility and processability of the material, reduce brittleness, and make the final product more flexible and adaptable to dynamic environments; butylated hydroxyanisole as an antioxidant can prevent the degradation of the polymer in high temperature or oxidative environments; polyethylene glycol as a solubilizer can improve the fluidity and uniformity of the mixture.
[0040] Because excessive moisture may cause bubbles to appear in the polymer during melting and reduce the physical properties of the finished product, polylactic acid, polyhydroxyalkanoate, chitosan and calcium carbonate powder are dried at 75-80°C for 3-4 hours to remove moisture from the raw materials and avoid the influence of moisture on material properties during subsequent mixing and processing;
[0041] The dried polylactic acid, polyhydroxyalkanoate, chitosan and calcium carbonate powder are uniformly mixed, and plasticizer, solubilizer and polyurethane are added in sequence, so that the various components can be effectively dispersed, the mutual agglomeration between polymers is reduced, and the overall performance of the material is improved.
[0042] In step S2, the mixture is heated to a molten state, cooled, and pelletized. Specifically, the mixture is placed in a twin-screw extruder, heated to a molten state at 150-170° C., and at the same time, the shear rate is controlled at 150-175 rpm to enhance the dispersion and interaction of the components in the mixture at high temperature;
[0043] Melt blending can promote uniform dispersion of various materials and avoid agglomeration in the materials. High temperature and shearing can enhance the interfacial interaction between materials, improve the compatibility between the polymer matrix and chitosan and polyurethane, and help form a more stable composite material.
[0044] In the molten state, after the mixture is extruded, it is rapidly cooled at a rate of 15-25℃ / min to form a solid, avoiding crystallization of the material during the cooling process and ensuring that the final product maintains flexibility and integrity;
[0045] The cooled mixture is cut into small particles to form pellets that are easy to handle and can be conveniently fed into the injection molding machine for subsequent molding processing, thereby improving production efficiency.
[0046] In step S3, the pellets after cutting are placed in an injection molding machine, wherein the weight portion of the plasticizer in the pellets is controlled to be 7-9 parts, so that the interaction force between the polymer chains is weakened, thereby increasing the flexibility and ductility of the sub-bags, and the injection molding temperature is set between 150-160° C., while heating the pellets to a molten state, it is possible to avoid excessive cross-linking of the polymer chains due to excessively high temperatures, thereby retaining a certain degree of flexibility;
[0047] The weight of the solubilizer is controlled at 5-10 parts. By increasing the content of the solubilizer, the fluidity and dispersibility of the polymer are effectively improved, and the solubilizer is evenly distributed in the polymer matrix to form a uniform polymer network, thereby reducing the turbidity of the material and improving the transparency of the subsequent prepared sub-bags.
[0048] After the pellets are heated to a molten state, the injection pressure is between 80-100MPa to ensure that the molten pellets are effectively injected into the mold and filled and formed. The injection pressure is controlled to ensure that the molecular structure in the bag is relatively loose, thereby improving the softness of the sub-bag;
[0049] After forming, the sub-bag product is quickly cooled to room temperature of 25-28°C at a rate of 15-20°C / min to avoid material crystallization and maintain greater mobility of the molecular chain, which helps to generate flexible sub-bags;
[0050] In step S4, the polytetrafluoroethylene coating has hydrophobicity and corrosion resistance. When applied as a coating on the surface of the urine storage bag, the physical properties of the urine storage bag can be significantly improved. Specifically, the low surface energy characteristics of the polytetrafluoroethylene coating make it difficult for water molecules to adhere, thereby reducing the contact between urine and the surface of the urine storage bag, thereby reducing the risk of urine retention and bacterial growth;
[0051] The sub-bag coated with polytetrafluoroethylene is heated at 150-160°C for 10-20 minutes. The increase in temperature intensifies the molecular movement of the polytetrafluoroethylene coating and the sub-bag, and the polytetrafluoroethylene coating can better penetrate into the surface microscopic pores and structures of the resin substrate, increasing the contact area between the two and forming a mechanical interlocking effect, so that the polytetrafluoroethylene coating forms a stable physical adsorption layer, thereby enhancing the combination of the two.
[0052] At the same time, under high temperature conditions, the hydroxyl groups in the polymer in the sub-bag react with the carboxyl groups on the surface of the polytetrafluoroethylene coating to form ester bonds, which enhance the mobility and fluidity of the polyurethane and other polymer chains, and also enhance the reactivity of the polyurethane, so that the polymer chains of the polyurethane can be cross-linked to form a three-dimensional network structure, which can fill the microscopic defects and irregular shapes of the polytetrafluoroethylene coating, thereby forming a dense bonding interface and enhancing the bonding force with the polytetrafluoroethylene coating.
[0053] In step S5, a mother bag is prepared with the same material as the sub-bag, and the weight of the plasticizer, the injection temperature, the injection pressure and the cooling rate are controlled to change the mechanical strength of the mother bag and prepare a hard mother bag. Specifically, polylactic acid, polyhydroxyalkanoate, chitosan and calcium carbonate powder are dried at 75-80° C. for 3-4 hours to remove moisture from the raw materials to avoid the influence of moisture on material properties during subsequent mixing and processing;
[0054] The dried polylactic acid, polyhydroxyalkanoate, chitosan and calcium carbonate powder are uniformly mixed, and plasticizer, solubilizer and polyurethane are added in sequence, so that the various components can be effectively dispersed, the mutual agglomeration between polymers is reduced, and the overall performance of the material is improved;
[0055] The mixture is heated to a molten state, cooled, and pelletized. Specifically, the mixture is placed in a twin-screw extruder, heated to a molten state at 150-170° C., and at the same time, the shear rate is controlled at 150-175 rpm to enhance the dispersion and interaction of the components in the mixture at high temperature;
[0056] The cut pellets are placed in an injection molding machine, wherein the weight portion of the plasticizer in the pellets is controlled to be 4-6 parts, so that the interaction force between the polymer chains is enhanced, thereby increasing the mechanical properties of the mother bag. The injection molding temperature is set between 170-190° C., and the pellets are heated to a molten state, while the high temperature promotes the full cross-linking of the polymer chains, thereby enhancing the mechanical properties of the mother bag;
[0057] The weight portion of the solubilizer is controlled at 2-4 parts. The content of the solubilizer is low, and chitosan increases the turbidity of the mixture, which will make the subsequently prepared mother bag product opaque. This is mainly because the low content of the solubilizer cannot effectively improve the fluidity and dispersibility of the polymer, thereby failing to form a uniform mixture.
[0058] After the pellets are heated to a molten state, the injection pressure is between 100-120MPa to ensure that the molten pellets are effectively injected into the mold and filled and formed. The injection pressure is controlled to ensure that the molecular structure in the bag is relatively tight, increase the density and hardness, and improve the hardness of the mother bag;
[0059] After molding, the mother bag product is quickly cooled to room temperature of 25-28°C at a rate of 8-14°C / min to promote material crystallization, which helps to generate a hard mother bag.
[0060] The present invention installs the formed mother bag and child bag into a mother-child urine storage bag through a one-way liquid valve, which not only prevents liquid reflux, but also prevents gas reflux, further avoiding the upward diffusion of pathogenic functional groups along the urethra, bladder, ureter and other urinary system mucosa of the patient, causing biochemical stimulation to the patient's urethra, bladder, ureter and other urinary system mucosa, resulting in the possibility of urinary system infection or immune lesions in the patient;
[0061] The patient's urethra passes through the sub-bag. Due to the coating of the polytetrafluoroethylene coating, the chemical properties of the surface of the sub-bag are changed, the surface energy of the sub-bag is reduced, and water molecules are more difficult to adhere to its surface, the hydrophobicity is improved, and urine is effectively prevented from hanging on the wall, so that urine can flow more smoothly into the mother bag, and at the same time, the long-term contact between urine and the sub-bag is reduced, reducing the risk of infection and inflammation; and the coating of the polytetrafluoroethylene coating avoids direct contact between the sub-bag and urine, and avoids the flexible sub-bag from precipitating some toxic or pathogenic functional groups in the environment of urine, while improving the comfort of the patient;
[0062] By setting the mother bag as a hard structure, the corrosion resistance and structural stability of the mother bag are further enhanced, and at the same time, the environmental pathogens in the mother bag can be inhibited. The hard mother bag can prevent deformation or kinking, which makes it difficult for urine from the sub-bag to enter the mother bag. Embodiment 1
[0063] 40 parts of polylactic acid, 20 parts of polyhydroxyalkanoate, 3 parts of chitosan and 1 part of calcium carbonate powder are dried at 80°C for 3h to remove moisture from the raw materials, and 8 parts of ethylene glycol dibenzoate, 8 parts of polyethylene glycol, 0.2 parts of butylated hydroxyanisole and 3 parts of polyurethane are added in sequence and mixed evenly to obtain a mixture, the mixture is put into a twin-screw extruder and heated to a molten state of 160°C. At the same time, the shear rate is controlled at 155rpm to enhance the dispersion and interaction of the components in the mixture at high temperature. In the molten state, the mixture is extruded and then rapidly cooled at a rate of 20°C / min to form a solid, and the cooled mixture is cut into small particles to form pellets that are easy to handle;
[0064] The cut pellets are placed in an injection molding machine, the injection molding temperature is set between 150°C, the pellets are heated to a molten state, and the injection molding pressure is between 80MPa, so that the molten pellets are injected into the mold and filled and molded. After molding, the sub-bag product is quickly cooled to a room temperature of 25-28°C at a rate of 20°C / min to obtain a transparent and flexible sub-bag product 1, and the surface of the sub-bag is evenly coated with a polytetrafluoroethylene coating, and heated at a temperature of 155°C for 15 minutes to obtain a sub-bag. Embodiment 2
[0065] 40 parts of polylactic acid, 20 parts of polyhydroxyalkanoate, 3 parts of chitosan and 1 part of calcium carbonate powder are dried at 80°C for 3h to remove moisture from the raw materials, and 8 parts of ethylene glycol dibenzoate, 8 parts of polyethylene glycol, 0.2 parts of butylated hydroxyanisole and 5 parts of polyurethane are added in sequence and mixed evenly to obtain a mixture, the mixture is put into a twin-screw extruder and heated to a molten state of 160°C. At the same time, the shear rate is controlled at 155rpm to enhance the dispersion and interaction of the components in the mixture at high temperature. In the molten state, the mixture is extruded and then rapidly cooled at a rate of 20°C / min to form a solid, and the cooled mixture is cut into small particles to form pellets that are easy to handle;
[0066] The cut pellets are placed in an injection molding machine, the injection temperature is set between 150°C, the pellets are heated to a molten state, and the injection pressure is between 80MPa, so that the molten pellets are injected into the mold and filled and formed. After molding, the sub-bag product is quickly cooled to a room temperature of 25-28°C at a rate of 20°C / min to obtain a transparent and flexible sub-bag product 2, and the surface of the sub-bag is evenly coated with a polytetrafluoroethylene coating, and heated at a temperature of 155°C for 15 minutes to obtain a sub-bag. Embodiment 3
[0067] 40 parts of polylactic acid, 20 parts of polyhydroxyalkanoate, 3 parts of chitosan and 1 part of calcium carbonate powder are dried at 80°C for 3h to remove moisture from the raw materials, and 8 parts of ethylene glycol dibenzoate, 8 parts of polyethylene glycol, 0.2 parts of butylated hydroxyanisole and 7 parts of polyurethane are added in sequence and mixed evenly to obtain a mixture, the mixture is put into a twin-screw extruder and heated to a molten state of 160°C. At the same time, the shear rate is controlled at 155rpm to enhance the dispersion and interaction of the components in the mixture at high temperature. In the molten state, the mixture is rapidly cooled at a speed of 20°C / min after extrusion to form a solid, and the cooled mixture is cut into small particles to form pellets that are easy to handle;
[0068] The cut pellets are placed in an injection molding machine, the injection molding temperature is set between 150°C, the pellets are heated to a molten state, and the injection molding pressure is between 80MPa, so that the molten pellets are injected into the mold and filled and molded. After molding, the sub-bag product is quickly cooled to a room temperature of 25-28°C at a rate of 20°C / min to obtain a transparent and flexible sub-bag product 3, and the surface of the sub-bag is evenly coated with a polytetrafluoroethylene coating, and heated at a temperature of 155°C for 15 minutes to obtain a sub-bag. Embodiment 4
[0069] 40 parts of polylactic acid, 20 parts of polyhydroxyalkanoate, 3 parts of chitosan and 1 part of calcium carbonate powder are dried at 80°C for 3h to remove moisture from the raw materials, and 8 parts of ethylene glycol dibenzoate, 8 parts of polyethylene glycol, 0.2 parts of butylated hydroxyanisole and 5 parts of polyurethane are added in sequence and mixed evenly to obtain a mixture, the mixture is put into a twin-screw extruder and heated to a molten state of 160°C. At the same time, the shear rate is controlled at 155rpm to enhance the dispersion and interaction of the components in the mixture at high temperature. In the molten state, the mixture is extruded and then rapidly cooled at a rate of 20°C / min to form a solid, and the cooled mixture is cut into small particles to form pellets that are easy to handle;
[0070] The cut pellets are placed in an injection molding machine, the injection molding temperature is set between 150°C, the pellets are heated to a molten state, and the injection molding pressure is between 80MPa, so that the molten pellets are injected into the mold and filled and molded. After molding, the sub-bag product is quickly cooled to a room temperature of 25-28°C at a rate of 20°C / min to obtain a transparent and flexible sub-bag product 4, and the surface of the sub-bag is evenly coated with a polytetrafluoroethylene coating, and heated at a temperature of 155°C for 15 minutes to obtain a sub-bag. Embodiment 5
[0071] 40 parts of polylactic acid, 20 parts of polyhydroxyalkanoate, 3 parts of chitosan and 1 part of calcium carbonate powder are dried at 80°C for 3h to remove moisture from the raw materials, and 8 parts of ethylene glycol dibenzoate, 8 parts of polyethylene glycol, 0.2 parts of butylated hydroxyanisole and 5 parts of polyurethane are added in sequence and mixed evenly to obtain a mixture, the mixture is put into a twin-screw extruder and heated to a molten state of 160°C. At the same time, the shear rate is controlled at 155rpm to enhance the dispersion and interaction of the components in the mixture at high temperature. In the molten state, the mixture is extruded and then rapidly cooled at a rate of 20°C / min to form a solid, and the cooled mixture is cut into small particles to form pellets that are easy to handle;
[0072] The cut pellets are placed in an injection molding machine, the injection molding temperature is set between 155°C, the pellets are heated to a molten state, and the injection molding pressure is between 90MPa, so that the molten pellets are injected into the mold and filled and molded. After molding, the sub-bag product is quickly cooled to a room temperature of 25-28°C at a rate of 20°C / min to obtain a transparent and flexible sub-bag product 5, and the surface of the sub-bag is evenly coated with a polytetrafluoroethylene coating, and heated at a temperature of 155°C for 15 minutes to obtain a sub-bag. Embodiment 6
[0073] 40 parts of polylactic acid, 20 parts of polyhydroxyalkanoate, 3 parts of chitosan and 1 part of calcium carbonate powder are dried at 80°C for 3h to remove moisture from the raw materials, and 8 parts of ethylene glycol dibenzoate, 8 parts of polyethylene glycol, 0.2 parts of butylated hydroxyanisole and 5 parts of polyurethane are added in sequence and mixed evenly to obtain a mixture, the mixture is put into a twin-screw extruder and heated to a molten state of 160°C. At the same time, the shear rate is controlled at 155rpm to enhance the dispersion and interaction of the components in the mixture at high temperature. In the molten state, the mixture is extruded and then rapidly cooled at a rate of 20°C / min to form a solid, and the cooled mixture is cut into small particles to form pellets that are easy to handle;
[0074] The cut pellets are placed in an injection molding machine, the injection molding temperature is set between 160°C, the pellets are heated to a molten state, and the injection molding pressure is between 100MPa, so that the molten pellets are injected into the mold and filled and molded. After molding, the sub-bag product is quickly cooled to a room temperature of 25-28°C at a rate of 20°C / min to obtain a transparent and flexible sub-bag product 6, and the surface of the sub-bag is evenly coated with a polytetrafluoroethylene coating, and heated at a temperature of 155°C for 15 minutes to obtain a sub-bag. Embodiment 7
[0075] 40 parts of polylactic acid, 20 parts of polyhydroxyalkanoate, 3 parts of chitosan and 1 part of calcium carbonate powder are dried at 80°C for 3h to remove moisture from the raw materials, and 5 parts of ethylene glycol dibenzoate, 3 parts of polyethylene glycol, 0.2 parts of butylated hydroxyanisole and 5 parts of polyurethane are added in sequence and mixed evenly to obtain a mixture, the mixture is put into a twin-screw extruder and heated to a molten state of 160°C. At the same time, the shear rate is controlled at 155rpm to enhance the dispersion and interaction of the components in the mixture at high temperature. In the molten state, the mixture is extruded and then rapidly cooled at a rate of 20°C / min to form a solid, and the cooled mixture is cut into small particles to form pellets that are easy to handle;
[0076] The cut pellets are placed in an injection molding machine, the injection temperature is set between 170°C, the pellets are heated to a molten state, and the injection pressure is between 100MPa, so that the molten pellets are injected into the mold and filled and formed. After molding, the mother bag product is quickly cooled to room temperature of 25-28°C at a rate of 8°C / min to obtain an opaque and hard mother bag product. Embodiment 8
[0077] It is basically the same as Example 7, except that the injection molding temperature is set between 180°C and the injection molding pressure is set between 110MPa, so that the molten pellets are injected into the mold and filled and formed. After molding, the mother bag product is quickly cooled to room temperature of 25-28°C at a rate of 8°C / min to obtain an opaque and hard mother bag product. Embodiment 9
[0078] It is basically the same as Example 7, except that the injection molding temperature is set between 190°C and the injection molding pressure is set between 120MPa, so that the molten pellets are injected into the mold and filled and formed. After molding, the mother bag product is quickly cooled to room temperature of 25-28°C at a rate of 8°C / min to obtain an opaque hard mother bag product.
[0079] The effects of the sub-bags and the main bag obtained in Examples 1 to 9 were compared.
[0080] 1. Compare the sub-bag products 1-3 and the sub-bags after the polytetrafluoroethylene coating is completed in Examples 1 to 3, and evaluate their performance, as shown in Table 1;
[0081] 1. Use AATCC 100 standard to evaluate the material's ability to inhibit bacteria.
[0082] A. Select Escherichia coli and Staphylococcus aureus for culture, take an appropriate amount of pure cultured bacteria and inoculate them on nutrient agar medium, culture them at 37°C for 24 hours, dilute the cultured bacteria to about 1×10^8 CFU / mL with physiological saline to obtain inoculum;
[0083] B. Soak the sub-bag products 1-3 in the inoculation solution for 30 minutes respectively, ensuring that the sample surface is evenly in contact with the bacterial solution. Take out the soaked samples from the inoculation solution, gently rinse them with sterile saline to remove bacteria not attached to the surface, and collect the sterile saline after rinsing, and record the colony count F1;
[0084] C. Perform the same operations as steps A and B above on the existing urine storage bag and record the colony count F2.
[0085] Calculate the antibacterial rate: Antibacterial rate = (F2-F1) / F2.
[0086] 2. For the sub-bags coated with polytetrafluoroethylene in Examples 1 to 3, use a tensile testing machine to clamp the polytetrafluoroethylene coating and the sub-bags respectively, start the tensile testing machine, gradually apply tensile force, record the maximum load of the sample peeling, and record.
[0087] Table 1
[0088]
[0089] By comparing the above-mentioned sub-bag products 1-3, it can be concluded that the antibacterial properties of the prepared sub-bag products are better as the content of polyurethane increases. This is mainly because the hydroxyl groups in the polyurethane and the polymer can react with the carboxyl groups of chitosan to form ester bonds, which increases the chemical compatibility of chitosan and the matrix, and the generated ester bonds enhance the interaction between chitosan and the polymer matrix, reduce the interfacial tension of chitosan in the matrix, and make it easier to disperse evenly in the polymer matrix, which contributes to the long-term release and durability of the antibacterial components of chitosan. However, as the content of polyurethane increases too much, the antibacterial properties of the prepared sub-bag products decrease. This is mainly because the excessive increase in the content of polyurethane leads to an increase in the overall density of the material, which may inhibit the uniform distribution of chitosan and reduce its dispersibility in the matrix. In addition, too much polyurethane may form a strong cross-linked structure with other components, reducing the interaction between chitosan and the matrix, resulting in a decrease in the efficiency of chitosan in releasing antibacterial components.
[0090] The sub-bags obtained in Examples 1 to 3 have further improved antibacterial properties, mainly because the low surface energy characteristics of the polytetrafluoroethylene coating make it difficult for water molecules to adhere, reducing the contact between urine and the surface of the urine storage bag, thereby reducing the risk of urine retention and bacterial growth; at the same time, as the content of polyurethane increases, the bonding strength between the polytetrafluoroethylene coating and the sub-bag becomes higher, mainly because the increase in the degree intensifies the molecular motion of the polytetrafluoroethylene coating and the sub-bag, and the polytetrafluoroethylene coating can better penetrate into the surface microscopic pores and structures of the resin substrate, increasing the contact area between the two, forming a mechanical interlocking effect, so that the polytetrafluoroethylene coating forms a stable physical adsorption layer, thereby enhancing the bonding between the two;
[0091] Under high temperature conditions, the hydroxyl groups in the polymer in the sub-bag react with the carboxyl groups on the surface of the polytetrafluoroethylene coating to form ester bonds, thereby enhancing the mobility and fluidity of the polyurethane and other polymer chains, and also enhancing the reactivity of the polyurethane, so that the polymer chains of the polyurethane can be cross-linked to form a three-dimensional network structure, which can fill the microscopic defects and irregular shapes of the polytetrafluoroethylene coating, thereby forming a dense bonding interface and enhancing the bonding force with the polytetrafluoroethylene coating. In summary, the sub-bag obtained in Example 2 is the optimal solution.
[0092] 2. Comparison of the performance tests between the sub-bags (sub-bag products coated with polytetrafluoroethylene coating) obtained in Examples 1 to 9, the mother bag products, and the existing urine storage bags, wherein the existing urine storage bag is specifically the type A anti-backflow urine storage bag of Yangzhou Guilong Medical Instrument Co., Ltd.;
[0093] 1. Corrosion resistance test: Soak the sub-bag (coated with polytetrafluoroethylene), the mother bag product and the existing urine storage bag in solutions with different pH values (e.g., pH 4, pH 6, pH 8) for 2.5 hours respectively, measure the mass of the sub-bag (coated with polytetrafluoroethylene), the mother bag product and the existing urine storage bag before and after immersion in solutions with different pH values for 2.5 hours, and obtain the mass loss rate of the material, where mass loss rate = (initial mass - mass after test) / initial mass × 100%.
[0094] 2.Hardness test: Use Rockwell hardness tester to test the hardness.
[0095] The following test data are obtained, as shown in Table 2;
[0096] Table 2
[0097]
[0098] In summary, it can be concluded that the sub-bags and mother bags prepared by the present invention have high corrosion resistance, mainly because the polyurethane is mixed with the substrate, an esterification reaction occurs, and the generated polymer, the hydroxyl and isocyanate contained in the polyurethane form ester bonds and amino bonds in the reaction, and during the reaction, the group not only reacts with the hydroxyl and carboxyl functional groups in the substrate, but also cross-links with the functional groups in other polyurethane molecules to form a three-dimensional network structure, wherein the group and the functional group cross-linking points connect different polymer chains through covalent bonds to form a three-dimensional cross-linked network structure, which not only enhances the mechanical strength of the material, but also improves its resistance to chemical corrosion, and the polytetrafluoroethylene coating has high corrosion resistance; at the same time, by controlling the weight of the plasticizer, the cooling temperature, the injection molding pressure and the injection molding temperature, the hardness of the sub-bag and the mother bag can be changed.
[0099] The sub-bag obtained in Example 2 and the mother bag in Example 8 were selected and installed through a one-way liquid valve, and tested with the existing urine storage bag;
[0100] 1. Test Preparation
[0101] A total of 110 inpatients with indwelling urinary catheters in a Beijing hospital from October 2022 to March 2024 were selected, including 79 males and 31 females, aged 18 to 80 years old, and were divided into ten groups according to the random number table method, with 11 people in each group. Inclusion criteria: patients with indwelling urinary catheters for ≥7 days; patients diagnosed with urinary tract infection and abnormal urine routine before catheterization were excluded.
[0102] 2. Test operation
[0103] The selected cases were divided into two groups according to their numbers: the odd-numbered cases were the experimental group, which consisted of 55 people, and used the urine storage bag of the present invention, and the urine bag was changed once a week; the even-numbered cases were the control group, which consisted of 55 people, and used the existing urine storage bag, and the urine bag was changed once every 4 days.
[0104] Starting from the day the patient has an indwelling urinary catheter, urine specimens are collected once on the 4th day and the 7th day, both at around 08:30 every day. The operator wears sterile gloves and uses an iodine cotton swab to disinfect the bifurcation of the catheter where the catheter and the urine bag are connected twice in a spiral manner. 5 ml of urine is drawn with a sterile syringe and injected into the specimen container for immediate bacterial culture. Each time the operator collects a specimen, he or she must observe and record the patient's body temperature, urine properties, and symptoms such as urinary tract irritation, and track the specimen culture results in a timely manner. If the urine culture is positive, the test is terminated, and further bacterial microbiological identification and cause analysis are performed.
[0105] The number of patients with urinary tract infection on the 4th and 7th days in the two groups was compared as shown in Table 3;
[0106] Table 3
[0107]
[0108] In summary, through the comparison between the test group and the control group, it can be concluded that the urine storage bag prepared by the present invention has better antibacterial performance.
[0109] A mother-child urine storage bag, comprising: a child bag and a mother bag, and a one-way liquid valve connecting the child bag and the mother bag; the child bag and the mother bag are both made of the following raw materials in parts by weight: 40-50 parts of polylactic acid, 20-25 parts of polyhydroxyalkanoate, 3-5 parts of chitosan, 4-9 parts of ethylene glycol dibenzoate, 2-10 parts of polyethylene glycol, 1-2 parts of calcium carbonate micropowder, and 3-7 parts of polyurethane.
[0110] The above is based on the ideal embodiment of the present invention. Through the above description, relevant personnel can make various changes and modifications without departing from the technical concept of the present invention. The technical scope of the present invention is not limited to the content in the specification, and the technical scope must be determined according to the scope of the claims.
Claims
1. A method for preparing a mother-child urine storage bag, characterized in that: The following steps are involved: Step S1, using 40-50 parts by weight of polylactic acid and 20-25 parts by weight of polyhydroxyalkanoate as a substrate, adding 3-5 parts by weight of chitosan, 0.1-0.5 parts of an antioxidant, and 1-2 parts of calcium carbonate powder for drying, and mixing them evenly after drying to obtain a mixed solid material, and sequentially adding a plasticizer, a solubilizer, and 3-7 parts by weight of polyurethane to the mixed solid material, and controlling the weight parts of the plasticizer and the solubilizer, and mixing them evenly to obtain a mixture; Step S2, heating the mixture to a molten state, cooling it, and pelletizing it; Step S3, pouring the pellets into an injection molding machine, controlling the injection molding temperature to a molten state, controlling the injection molding pressure, pressurizing the molten pellets, and then cooling to room temperature to obtain a transparent and flexible sub-bag product; Step S4, washing and drying the transparent and flexible sub-bag product, coating the surface with a polytetrafluoroethylene coating, and subjecting the sub-bag coated with the polytetrafluoroethylene coating to a heat-curing treatment; Step S5, repeating the operations of step S1, step S2 and step S3 with the material for preparing the urine storage bag, and controlling the weight of the plasticizer, the weight of the solubilizer, the injection temperature and the injection pressure, performing pressure molding and then cooling to room temperature to obtain an opaque and hard mother bag product; In the step S1, the plasticizer is ethylene glycol dibenzoate, the antioxidant is butylated hydroxyanisole, and the solubilizer is polyethylene glycol.
2. The method for preparing a mother-and-child urine storage bag according to claim 1, characterized in that: In the step S1, the weight portion of the plasticizer is 7-9 parts, and the weight portion of the solubilizer is 5-10 parts.
3. The method for preparing a mother-and-child urine storage bag according to claim 1, characterized in that: In the step S1, the drying process is specifically drying at 75-80° C. for 3-4 hours.
4. The method for preparing a mother-and-child urine storage bag according to claim 1, characterized in that: In step S3, the pellets are poured into an injection molding machine, heated to a molten state at an injection molding temperature between 150-160° C., the pressure is controlled at 80-100 MPa, and then cooled to a room temperature of 25-28° C. after pressure molding.
5. The method for preparing a mother-and-child urine storage bag according to claim 1, characterized in that: In the step S2, the mixture is fed into a twin-screw extruder for melt blending, the heating temperature is between 150-170°C, and the shear rate is controlled at 150-175rpm.
6. The method for preparing a mother-and-child urine storage bag according to claim 1, characterized in that: In the step S4, the thermosetting treatment comprises: heating the sub-bag coated with the polytetrafluoroethylene coating at a temperature of 150-160° C. for 10-20 minutes.
7. The method for preparing a mother-and-child urine storage bag according to claim 1, characterized in that: In step S5, the weight portion of the plasticizer is 4-6 parts, the weight portion of the solubilizer is 2-4 parts, the injection molding temperature is between 170-190° C., and the injection molding pressure is 100-120 MPa.
8. A mother-and-child urine storage bag, based on the method for preparing a mother-and-child urine storage bag according to claim 1, characterized in that: The urine storage bag comprises: a sub-bag and a main bag, and a one-way liquid valve connecting the sub-bag and the main bag; the sub-bag and the main bag are both made of the following raw materials in parts by weight: 40-50 parts of polylactic acid, 20-25 parts of polyhydroxyalkanoate, 3-5 parts of chitosan, 4-9 parts of ethylene glycol dibenzoate, 2-10 parts of polyethylene glycol, 0.1-0.5 parts of butylated hydroxyanisole, 1-2 parts of calcium carbonate micropowder, and 3-7 parts of polyurethane.
9. The mother-and-child urine storage bag according to claim 8, characterized in that: The sub-bag and the main bag are both made of the following raw materials in parts by weight: 40 parts of polylactic acid, 20 parts of polyhydroxyalkanoate, 3 parts of chitosan, 4 parts of ethylene glycol dibenzoate, 2 parts of polyethylene glycol, 0.1 parts of butylated hydroxyanisole, 1 part of calcium carbonate micropowder, and 3 parts of polyurethane.
Citation Information
Patent Citations
Degradable disposable catheterization bag material and preparation method thereof
CN110305455A
Polycarbonate resin composition, molded article and multi-layer body
CN112262178A